1992
DOI: 10.1136/jech.46.3.248
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia in Croatia: interregional differences in prevalence and a comment on constant incidence.

Abstract: Study objective-The aim was to examine why differences exist in schizophrenia prevalence and risk in some areas of Croatia, when schizophrenia incidence rates do not appear to vary.Design-Areas differing by schizophrenia admission rates in patients born in 1953 and admitted by the age of 31 years are compared using a number of indicators relating both to general population characteristics and to those of schizophrenic cases in these populations.Setting-The study covers the whole of Croatia (4 601

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…In the United States, the rates of hospital-treated mental illnesses and schizophrenia, measured in 9 separate years between 1880 and 1963, were consistently higher in Northeastern and Pacific Coast States compared with the rest of the country (Torrey, 1990). In Croatia, the cumulative incidence of schizophrenia among the population born in 1953 was highest in southern, coastal parts of the country and lowest in eastern, inland parts of the country (Folnegovic & Folnegovic-Smalc, 1992). An Irish study conducted in an isolated rural county found evidence of geographic variation (Youssef et al 1991) that was more prominent among females than males (Youssef et al 1993).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the United States, the rates of hospital-treated mental illnesses and schizophrenia, measured in 9 separate years between 1880 and 1963, were consistently higher in Northeastern and Pacific Coast States compared with the rest of the country (Torrey, 1990). In Croatia, the cumulative incidence of schizophrenia among the population born in 1953 was highest in southern, coastal parts of the country and lowest in eastern, inland parts of the country (Folnegovic & Folnegovic-Smalc, 1992). An Irish study conducted in an isolated rural county found evidence of geographic variation (Youssef et al 1991) that was more prominent among females than males (Youssef et al 1993).…”
Section: Introductionmentioning
confidence: 94%
“…If these differences are caused by an uneven distribution of risk factors for schizophrenia, they are of considerable significance to aetiological research. However, the observed differences may also have resulted from variations in diagnostic practice (Leff, 1977), problems in defining the population denominators for subgroups (Mortensen et al 1997), or by selective migration (Folnegovic & Folnegovic-Smalc, 1992 ;Freeman, 1994). In fact, the opinion that the incidence of schizophrenia is uniform across cultures is widely held (Jablensky et al 1992 ;McGlashan & Hoffman, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…But a recent study (Folnegovic and Folnegovic-Smalc, 1992) aimed at investigating differences in prevalence rates in different parts of Croatia concluded that economic migration and negative selection in the domestic population were likely to be the most significant factors in differences in prevalence. Reviewing these findings Cooper (1994) concluded that 'nosocomial factors, combined with the effects of selective migration, would seem on present evidence to offer a more likely explanation' of the observed variation.…”
Section: Constancy Of Incidence Over Time and Place: 'The Anthropo-pamentioning
confidence: 99%
“…Por último, se sabe que las personas nacidas en pleno invierno presentan un mayor riesgo de esquizofrenia que otras (21)(22)(23). Acaso como resultado de estos u otros factores, a veces se constata una variación geográfica de la prevalencia de esquizofrenia en un país (24,25).…”
Section: Tasas De Ingreso Inicial Por Esquizofrenia En Hospitales De unclassified